Temporal change in urinary parameters and Ultrastructural pathology of kidney in cisplatin Induced nephrotoxicity in rats - VENKATESHA UDUPA; VEERU PRAKASH (International Journal of Pharma and Bio Sciences, 2018)
This study was undertaken to evaluate dose and time dependent changes in urinary parameters and ultrastructure of kidneys in Cisplatin induced nephrotoxicity in male Sprague Dawley rats. Single intraperitoneal dose of Cisplatin was administered to male Sprague Dawley rats at 2.5 and 5 mg/kg. On day 4 and day 8 post treatment, urine and kidney samples were collected for investigation. On day 4 significant increase in urine pH at 2.5 mg/kg; decrease in creatinine at 2.5 mg/kg; decrease in creatinine clearance at 5.0 mg/kg; increase in albumin glucose and microalbumin (mALB); decrease in creatinine clearance in both 2.5 and 5.0 mg/kg were observed. On day 8, increased glucose and mALB and decreased calcium at 5.0 mg/kg; increased N-acetyl glucosamine and decreased creatinine and creatinine clearance in both 2.5 and 5.0 mg/kg were observed. Ultrastructural changes on day 4 included disintegrating pyknotic nucleus, indistinct and electron dense mitochondria, empty perinuclear cytoplasm, normal intertubular junction, mild margination of chromatin and streaky or elongated mitochondrial structure at 2.5 mg/kg, and severe tubular dilatation, disintegration of chromatin, swollen nucleus and indistinct cytoplasmic organelles at 5.0 mg/kg. On day 8, kidneys showed dilatation of foot process and variation in size and shape of podocytes, apoptotic nucleus, elongated mitochondria, discontinuous cisternae of rough endoplasmic reticulum and loose intracellular junction at 2.5 mg/kg, and severe disintegration of chromatin, presence of myeloid bodies and increased periglomerular space, loss of architecture of cytoplasmic organelles, karyorhexis, tubular epithelial degeneration, disintegration of nuclear material, perinuclear vacuoles, indistinct cytoplasmic organelles and minimal myeloid cells at 5.0 mg/kg. This study indicates diagnostic value of electron microscopy compared to evaluation of urinary parameters in identifying classical changes in mitochondria, increased periglomerular space, apoptotic nucleus and presence of myeloid bodies in Cisplatin induced nephrotoxicity in rats.